Does Access to Foreign Markets shape Internal Migration? Evidence from Brazil - Laura Hering; Rodrigo Paillacar (Tinbergen Institute, 2014)
This paper investigates how internal migration is a affected by Brazil's increased integration into the world economy. We analyze the impact of regional differences in access to foreign demand on sector-specific bilateral migration rates between the Brazilian states for the years 1995 to 2003. Using international trade data, we compute a foreign market access indicator at the sectoral level, which is exogenous to domestic migration. A higher foreign market access is associated with a higher local labor demand and attracts workers via two potential channels: higher wages and new job opportunities. Our results show that both channels play a significant role in internal migration. Further, we find a heterogeneous impact across industries according to their comparative advantage on the world market. However, the impact of market access is robust only for low-educated wor kers. This finding is consistent with the fact that Brazil is exporting mainly goods that are intensive in unskilled labor.
Keywords: F16; F66; R12; R23; 330; Regional migration; international trade; market access; Brazil